IMPLEMENTASI TEORI BELAJAR BEHAVIORISTIK DAN KOGNITIVISTIK DALAM RANCANGAN PEMBELAJARAN - Fariza, Fariza Zulfalillah; Herdiana, Dodi (Journal Of Education, 2024)
Learning theory can be interpreted as a systematic unity consisting of concepts, principles, and definitions related to how individuals acquire knowledge, skills, as well as changes in behaviour and character through learning process. Learning theory has an essential role, one of which is used as a conceptual and pedagogical reference to design an appropriate learning for students. This research focuses on behavioristic and cognitivistic learning theories that are implemented in learning design. Behavioristic learning theory emphasizes learning outcomes in the form of behavioral changes obtained through environmental conditioning, while cognitivistic learning theory emphasizes the information processing and understanding that individuals go through during learning rather than the final results obtained. These two theories have significantly different views, yet in the design of a lesson they can be collaborated since it complements each other in fulfilling learning objectives that can enhance individual understanding and skills. The research method used is library research by collecting various sources of literature related to the topic raised. Key words: design, design instructional, learning, behavioristic, cognitivistic.